Advanced glycation end products and human diseases - Hamad Abu Zahra (Journal of Biological Research)
Proteins, lipids, and nucleic acids can undergo non-enzymatic glycation and oxidation, leading to the formation of Advanced Glycation End products (AGEs). These chemically stable compounds accumulate in various tissues over time and are strongly implicated in the pathogenesis of several chronic human diseases, including cognitive impairment, diabetes, kidney failure, stroke, cardiac disease, and neurodegenerative disorders. AGEs contribute to the development of these conditions by forming cross-links between proteins, modifying cellular receptors, and inducing oxidative stress, which results in the functional compromise of biological molecules. As such, they are considered a hallmark of metabolic diseases, particularly those associated with aging and poor glycemic control. This review provides a comprehensive analysis of the role of AGEs in the etiology of vascular dysfunction, cognitive decline, renal impairment, cerebrovascular accidents, and cardiovascular disease. Additionally, the underlying cellular mechanisms by which AGEs exert their deleterious effects, including receptor-mediated signaling pathways, inflammation, and oxidative damage, are explored. Finally, the potential therapeutic strategies aimed at inhibiting AGE formation, breaking AGE cross-links, or blocking AGE receptors, highlighting their promise in mitigating AGE-associated pathologies, are discussed.